2018
DOI: 10.9734/jsrr/2017/38711
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Innovations: The Status of Building Information Modelling Uptake in Nigeria

Abstract: Aim: This study evaluated Building Information Modelling (BIM) awareness and adoption in Nigeria through the line of enquiry known as the 'diffusion of innovations' and its possible uptake. Study Design: The study is quantitative in nature and the primary data fetched through questionnaire survey within Nigerian construction industry. Place and Duration of the Study: Conducted within Northwest , North-central and Lagos, Nigeria for a period of 4 months. Methodology: A quantitative approach was adopted to x-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 8 publications
2
23
0
Order By: Relevance
“…However, the extent of BIM adoption in Nigeria is best described as stagnant (Ibrahim and Birshir, 2012). For instance, Hamma-adama et al (2017) stated that the current status of BIM uptake in Nigeria is predominantly by the usage of 2D and 3D. This is affirmed by Olugboyega and Aina (2018) who reported that both 2D and various variants of 3D BIM (such as 3D architectural model, 3D architectural and structural model and 3D architectural and building services model) are mostly used in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the extent of BIM adoption in Nigeria is best described as stagnant (Ibrahim and Birshir, 2012). For instance, Hamma-adama et al (2017) stated that the current status of BIM uptake in Nigeria is predominantly by the usage of 2D and 3D. This is affirmed by Olugboyega and Aina (2018) who reported that both 2D and various variants of 3D BIM (such as 3D architectural model, 3D architectural and structural model and 3D architectural and building services model) are mostly used in Nigeria.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In Nigeria, various studies on BIM have focused on awareness of BIM, adoption, benefits and challenges, both from the industry and academic perspectives (Ibironke et al , 2011; Abubakar et al , 2014; Ugochukwu et al , 2015; Hamma-adama et al , 2017; Onungwa et al , 2017; Babatunde et al , 2018; Babatunde and Ekundayo, 2019). A few of these studies have examined the barriers to BIM implementation (Abubakar et al , 2014; Babatunde and Ekundayo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies on BIM in Nigeria (Alufohai, 2012; Abubakar et al , 2014; Ryal-Net and Kaduma, 2015; Ugochukwu et al , 2015; Akerele and Etiene, 2016; Hamma-adama et al , 2017; Onungwa et al , 2017; Babatunde et al , 2018) have focussed on BIM awareness, adoption, implementation and challenges both from the industry and academia perspectives. Few of these studies that examined the drivers to BIM adoption (Babatunde et al , 2018) paid attention to the drivers to BIM incorporation into quantity surveying profession from academia and students’ perspectives; hence, the study (Babatunde et al , 2018) failed to examine the phenomenon from the industry stakeholders’ perspective.…”
Section: Introductionmentioning
confidence: 99%
“…Structured questionnaire was used as tool for data collection [6] hosted online using google forms. In addition, snowball method was adopted in targeting the survey respondents due to low level of BIM awareness and maturity in the country [12]. A few number of BIM experts volunteered to participate in the survey and subsequently more participants were recorded through them (initial respondents) -snowball.…”
Section: Nigerian Macro Maturity Modelmentioning
confidence: 99%